THE INFLUENCE OF WORK DISCIPLINE, LOYALTY, AND WORKLOAD ON EMPLOYEE PERFORMANCE AT PT INDOMARCO PRISMATAMA, SIMALINGKAR AREA, MEDAN SELAYANG. - Siregar, Elsa Nora; Lubis, Hidayati Purnama; Ario, Firman (JURNAL ILMIAH EDUNOMIKA, 2024)
This study is titled "The Influence of Work Discipline, Loyalty, and Workload on Employee Performance at PT. Indomarco Prismatama, Simalingkar Area, Medan Selayang." The method used in this research is associative with a quantitative approach. Data collection was done through questionnaires. The sample size for this study was 65 individuals. The data analysis techniques used in this research include descriptive statistical analysis, validity tests, reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity tests), multiple linear regression analysis, and hypothesis testing with t-tests and F-tests, as well as the determination coefficient test (RÂ²). The results show that partially (t-test), the work discipline variable (X1) has a positive and significant effect on the employee performance variable, with a t-value greater than the t-table value (2.815>1.99962) and a significance level of 0.0071.99962) and a significance level of 0.0071.99962) and a significance level of 0.0002.76) and a significance level of 0.000